Impact of rain attenuation on high altitude platform ststion backhaul link in Malaysia - Adeel Ghulam Nabi, author; Jafri Din, author; IEEE Regional Student Conference on Research and Development (2008: Skudai, Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL